Exploring The Interactions of a Natural Gamma-Oryzanol with Human Serum Albumin: Surface Plasmon Resonance, Fluorescence, and Molecular Modeling Studies - Maleki, Somaiyeh; Arabzadeh, AmirAhmad; Nejati, Kazem; Fathi, Farzaneh (Drug Research, 2021)
γ-oryzanol (ORY) is the vital bioactive compound, which is a mixture of ferulic acid ester and plant sterols. In the present work, the binding of ORY to human serum albumin (HSA) was investigated at the molecular level using fluorescence spectroscopy and surface plasmon resonance (SPR) as well as molecular modeling studies. Based on the fluorescence data analysis, ORY can form a non-fluorescent complex with HSA and induce static quenching of the emission intensity of HSA. Also, the high value of KSV (34.69 × 104 M−1) confirmed a high sensitivity of HSA toward ORY. The real-time monitoring of the binding of ORY to HSA was carried out using the SPR technique. The small KD value (1.23 × 10−6 M) calculated by SPR analysis indicated a high affinity of ORY toward HSA. The molecular modeling studies confirmed that ORY has only one binding site on HSA and binds HSA in a cavity between subdomain IIA and IIIA.
Keywords: Human serum albumin; γ-oryzanol; Surface plasmon resonance; Static quenching mechanism; Molecular docking